Verrucous Hemangioma Treated with Electrocautery - Mohammad Fatani; Homaid Al Otaibi; Muath Mohammed; Osama Hegazy (Karger Publishers, 2016)
Verrucous hemangioma is a rare vascular malformation consisting of a proliferation of dilated blood vessels of different sizes that occupy the dermis and hypodermis. The epidermis of the affected area shows a strong proliferative reaction that presents as a warty appearance. Here, we report the case of a 17-year-old male who presented with an asymptomatic warty growth above the lateral malleolus on the right leg, which healed after electrocautery.